Accurate in vivo real-time determination of the hydrogen concentration in different tissues of mice after hydrogen inhalation. Issue 10 (October 2022) - Zhu, Wenjun; Gu, Qianqian; Liu, Boyan; Si, Yanhong; Sun, Huirong; Zhong, Jingjie; Lu, Yi; Wang, Dan; Xue, Junli; Qin, Shucun
Abstract: As an antioxidant, anti-inflammatory and anti-apoptotic agent, hydrogen (H2 ) shows a promising potential in basic and clinical research against various diseases owing to its safety and efficacy. However, knowledge involving its underlying mechanisms of action, dosage effects, and dose duration remains limited. Previously, the dynamics of H2 concentrations in different tissues of rats after exogenous H2 inhalation had been detected by our team. Here, sequential changes of H2 concentrations in different tissues of another most commonly used experimental rodent mice were monitored in real time with an electrochemical H2 gas sensor during continuous different concentrations of H2 inhalation targeting on five tissues including brain, liver, spleen, kidney, and gastrocnemius. The results showed that the H2 saturation concentrations varied among tissues significantly regardless of the concentration of H2 inhaled, and they were detected the highest in the kidney but the lowest in the gastrocnemius. Meantime, it required a significant longer time to saturate in the thigh muscle. By comparing the H2 saturation concentrations of mice and rats, we found that there were no differences detected in most tissues except the kidney and spleen. Both gas diffusion and bloodstream transport could help the H2 reach to most organs. The results provide data reference for dosage selection, dose duration determination to ensure optimal therapeutic effects of H2 for mice experiments. Abstract : Hydrogen concentration; Real-time monitoring; Various tissues; electrochemical sensor; In vivo ; Mice.